2005
DOI: 10.1142/s0217732305017640
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino Asymmetry Around Black Holes: Neutrinos Interact With Gravity

Abstract: Propagation of a fermion in curved space-time generates a gravitational interaction due to coupling of its spin with the space-time curvature connection. This gravitational interaction, which is an axialfour-vector multiplied by a four gravitational vector potential, appears as a CPT violating term in the Lagrangian which generates an opposite sign and thus asymmetry between the left-handed and the right handed partners under the CPT transformation. In the case of neutrinos, this property can generate a neutri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 35 publications
2
60
0
Order By: Relevance
“…the function u a (r, t), which is involved in the spin evolution equations) of massless particles differs from that of massive particles. However in the case of massless particles the helicity and chirality are the same and one can apply the methods used in the recent work [26].…”
Section: Discussionmentioning
confidence: 99%
“…the function u a (r, t), which is involved in the spin evolution equations) of massless particles differs from that of massive particles. However in the case of massless particles the helicity and chirality are the same and one can apply the methods used in the recent work [26].…”
Section: Discussionmentioning
confidence: 99%
“…The various aspects of this feature have been studied in past (e.g., [4][5][6][7][8][9][10][11][12]). It has also been shown that this interaction may be responsible for an additional neutrino asymmetry even in the present era of universe [13][14][15]. However, it is very difficult to visualize as the strength of the above mentioned interaction is negligible in our earth which is practically flat.…”
mentioning
confidence: 99%
“…However, it is very difficult to visualize as the strength of the above mentioned interaction is negligible in our earth which is practically flat. In a similar fashion, the space-time around a black hole can generate neutrino asymmetry locally [13,15], but as we do not have overall information about number of black holes and their * ujjal@iucaa.ernet.in † bmukhopa@cfa.harvard.edu ‡ nkd@iucaa.ernet.in 1 corresponding spin orientation, it is very difficult to predict whether it produces a significant asymmetry over the relic value or not. A similar mechanism to produce asymmetry was noted earlier [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, one can obtain the oscillation phase δ from eqn. (8). If we consider a special case when S(t) = arbitrary constant = k, then B 0 , B 2 → 0 at t → ∞ 3 , which verifies that the curvature coupling is insignificant in the present universe to exhibit any such oscillation.…”
Section: A Early Universementioning
confidence: 62%